Reframing the Reclaiming of Urban Space: A Feminist Exploration into Do-It-Yourself Urbanism in Chicago. - LaFrombois, Megan E. Heim (Lexington Books (R and L) : Lexington Books, 2017)
Reframing the Reclaiming of Urban Space examines DIY urbanism from an intersectional feminist analytical framework. The racialized, classed, gendered, and sexualized aspects of DIY urbanism, including its activities, its actors, and its spaces are highlighted, as well as the connections between DIY urbanism and urban political agendas.